WHAT ABOUT THE CONVERSATION? THE LACK OF SOCIAL INTERACTION IN KINDLE WORLDS - Bothe, Jemma Sheree (AoIR Selected Papers of Internet Research, 2014)
Amazon has sought to commercialise and legitimise fan fiction (fanfic) through its Kindle Worlds project, established in May 2013. However, this project has only achieved limited success to date. This paper states that the Amazon platform does not allow for the underlying and constitutive dialogues that are as important as the product for many writers. In light of this I argue that the inherent sociality of fan fiction is unsuitable for consumerist contexts, and that it is unlikely that fiction writers will adopt the Kindle Worlds platform. The data for this paper has been collected over the last 6 months of fieldwork. Data has been collected through interviews, as well as through the observation of fanfic, and associated online fanfic sites.